Investigation of an Unrecorded Indigenous Copper Kettle Burial at Cap St-Louis, New Brunswick - Tremblay, Eric (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2021)
This article is the result of an investigation about an unrecorded archaeological find in Cap St-Louis (New Brunswick) in 1940. The find was a Copper Kettle Burial as it was practiced by the Mi’gmaq during the 16th and 17th century. No proper recording or conservation efforts had been deployed then since the Copper Kettle Burial was not well known at the time. Most of the funerary objects have been lost or given as mementos to family or friends of finder. The site has been eroded since 1940 but this investigation permitted Parks Canada to assign it a provenience number and ensure proper protection in the future for the site in case other burials appears at this location. Some objects are located at the Musée Acadien de l’Université de Moncton. In the spirit of reconciliation, the university will give back these funerary objects to the Mi’gmaq of New Brunswick.